Notes on the systematics of the Triaenonychinae from Madagascar with description of a new species of Acumontia Loman (Opiliones: Laniatores) - Mendes, Amanda C.; Kury, Adriano B. (Zootaxa, 2012)
Acumontia succinea sp. nov. is described from the Parc national de la Montagne d'Ambre, in the former Antsiranana Pro-vince, Madagascar. Detailed illustrations from all views of the male genitalia of a species of Acumontia are provided forthe first time. Complementary illustrations are provided of the types of the five valid species of Acumontia described by Pocock in the beginning of the 20th century, two of which had never been illustrated before.